Moderate organic fertilizer substitution for partial chemical fertilizer improved soil microbial carbon source utilization and bacterial community composition in rain-fed wheat fields: current year - Liu, Xiaoli; Yang, Wenping; Li, Wenguang; Ali, Aamir; Chen, Jie; Sun, Min; Gao, Zhiqiang; Yang, Zhenping (Frontiers in Microbiology, 2023)
Organic fertilizers can partially replace chemical fertilizers to improve agricultural production and reduce negative environmental impacts. To study the effect of organic fertilizer on soil microbial carbon source utilization and bacterial community composition in the field of rain-fed wheat, we conducted a field experiment from 2016 to 2017 in a completely randomized block design with four treatments: the control with 100% NPK compound fertilizer (N: P2O5: K2O = 20:10:10) of 750 kg/ha (CK), a combination of 60% NPK compound fertilizer with organic fertilizer of 150 kg/ha (FO1), 300 kg/ha (FO2), and 450 kg/ha (FO3), respectively. We investigated the yield, soil property, the utilization of 31 carbon sources by soil microbes, soil bacterial community composition, and function prediction at the maturation stage. The results showed that (1) compared with CK, organic fertilizer substitution treatments improved ear number per hectare (13%−26%), grain numbers per spike (8%−14%), 1000-grain weight (7%−9%), and yield (3%−7%). Organic fertilizer substitution treatments increased the total nitrogen, available nitrogen, available phosphorus, and soil organic matter contents by 26%, 102%, 12%, and 26%, respectively, compared with CK treatments. Organic fertilizer substitution treatments significantly advanced the partial productivity of fertilizers. (2) Carbohydrates and amino acids were found to be the most sensitive carbon sources for soil microorganisms in different treatments. Particularly for FO3 treatment, the utilization of β-Methyl D-Glucoside, L-Asparagine acid, and glycogen by soil microorganisms was higher than other treatments and positively correlated with soil nutrients and wheat yield. (3) Compared with CK, organic fertilizer substitution treatments increased the relative abundance of Proteobacteria, Acidobacteria, and Gemmatimonadetes and decreased the relative abundance of Actinobacteria and Firmicutes. Interestingly, FO3 treatment improved the relative abundance of Nitrosovibrio, Kaistobacter, Balneimonas, Skermanella, Pseudomonas, and Burkholderia belonging to Proteobacteria and significantly boosted the relative abundance of function gene K02433 [the aspartyl-tRNA (Asn)/glutamyl-tRNA (Gln)]. Based on the abovementioned findings, we suggest FO3 as the most appropriate organic substitution method in rain-fed wheat fields.